2000
DOI: 10.1071/sr99091
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying variability of soil physical properties within soil series to address modern land-use issues on the Canterbury Plains, New Zealand

Abstract: Lack of accurate data to estimate soil physical properties for soil types is limiting the wide application of simulation models to address modern environmental and land-use issues. In this study, systematic sampling of soil profiles for soil physical characteristics has provided an improved basis upon which to estimate a number of soil physical properties for 4 soil series. The selected soils form a soil drainage sequence on the post-glacial surface of the Canterbury Plains and vary from shallow sandy loam, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…For example, BD had the lowest CV (8%), particle size distribution and SWC had medium CVs (15 to 44%), and Ksat had the highest CV (102%). Kvaerno and Deelstra (2002) also reported high variability of Ksat in a silty clay loam in southeastern Norway, and high CVs for Ksat have also been documented by other investigators (Jury, 1989;Tsegaye and Hill, 1998;Webb et al, 2000;Shukla et al, 2004).…”
Section: Descriptive Statistics and Geostatistical Parametersmentioning
confidence: 65%
“…For example, BD had the lowest CV (8%), particle size distribution and SWC had medium CVs (15 to 44%), and Ksat had the highest CV (102%). Kvaerno and Deelstra (2002) also reported high variability of Ksat in a silty clay loam in southeastern Norway, and high CVs for Ksat have also been documented by other investigators (Jury, 1989;Tsegaye and Hill, 1998;Webb et al, 2000;Shukla et al, 2004).…”
Section: Descriptive Statistics and Geostatistical Parametersmentioning
confidence: 65%
“…This is also recognized for New Zealand soils, both due to the high variability over short distances in soil parent material, age, depth, and texture, as well as strong macropore development with preferential macropore flow recognized as the norm rather than the exception in New Zealand soils (Webb et al, 2000;Carrick, 2009;McLeod et al, 2008). The measurement variability is also expected to increase as the sampling diameter decreases because small cores provide an unrealistic representation of the abundance and connectivity of macropores (McKenzie and Cresswell, 2002;Anderson and Bouma, 1973).…”
Section: Introductionmentioning
confidence: 88%
“…In the first data set (Canterbury Regional Study; Table 4), soils were derived from eight soil series on the postglacial and glacial alluvial fan surfaces of the Canterbury Plains (Webb et al, 2000). The soils varied from shallow, well-drained silt loam soils to deep, poorly drained clay loam soils.…”
Section: Measurement Of Physical Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unhappily, this standard of map purity has rarely been attained. Studies have shown that there is considerable variability in soil properties and soil types within soil map units on alluvial plains in New Zealand (Adams and Wilde, 1976;Di and Kemp, 1989;Karageorgis, 1980;Webb et al, 2000). In general, knowledge of soil variability gained in the course of soil surveys has not been captured on the resulting soil maps and reports.…”
Section: New Zealandmentioning
confidence: 97%